Copper@ZIF‐8 Core‐Shell Nanowires for Reusable Antimicrobial Face Masks. (13th December 2020) - Kumar, Abhishek; Sharma, Anu; Chen, Yi; Jones, Megan M.; Vanyo, Stephen T.; Li, Changning; Visser, Michelle B.; Mahajan, Supriya D.; Sharma, Rakesh Kumar; Swihart, Mark T.
Abstract: SARS‐CoV‐2 and other respiratory viruses spread via aerosols generated by infected people. Face masks can limit transmission. However, widespread use of disposable masks consumes tremendous resources and generates waste. Here, a novel material for treating blown polypropylene filtration media used in medical‐grade masks to impart antimicrobial activity is reported. To produce thin copper@ZIF‐8 core‐shell nanowires (Cu@ZIF‐8 NWs), Cu NWs are stabilized using a pluronic F‐127 block copolymer, followed by growth of ZIF‐8 to obtain uniform core‐shell structures. The Cu@ZIF‐8 NWs are applied to filtration media by dip coating. Aerosol filtration efficiency decreases upon exposure to ethanol (solvent for dip‐coating), but increases with addition of Cu@ZIF‐8 NWs. Cu@ZIF‐8 NWs shows enhanced antibacterial activity, compared to Cu NWs or ZIF‐8 alone, against Streptococcus mutans and Escherichia coli . Antiviral activity against SARS‐CoV‐2 is assayed using virus‐infected Vero E6 cells, demonstrating 55% inhibition of virus replication after 48 h by 1 µg of Cu@ZIF‐8 NWs per well. Cu@ZIF‐8 NWs' cytotoxicity is tested against four cell lines, and their effect on inflammatory response in A549 cells is examined, demonstrating good biocompatibility. This low‐cost, scalable synthesis and straightforward deposition of Cu@ZIF‐8 NWs onto filter media has great potential to reduce disease transmission, resource consumption, and environmental impact of waste. Abstract : Antimicrobial copper nanowires coated with ZIF‐8 metal organic framework (Cu@ZIF‐8 NWs) are prepared and applied to blown polypropylene filter media typically used in face masks. The Cu@ZIF‐8 NWs and treated mask material show enhanced antimicrobial activity that can enable their use in self‐sanitizing reusable face masks and other medical textiles to reduce transmission of disease, including COVID‐19.